Learning Teaching Factory Reviewed from POAC Management on the Competence of Engineering and Motorcycle Business Expertise SMK - Santoso, Teguh; Yoto, Yoto; Nurhadi, Didik (Budapest International Research and Critics University, 2021)
This research aims to get an in-depth overview of the management of the implementation of Teaching Factory Competence of Engineering Expertise and Motorcycle Business Vocational High School in Tulungagung Regency of East Java. Who is expected to find and describe the data in detail about the cooperation of the Vocational High School with the business world and the industrial world to prepare a skilled workforce through the Teaching Factory learning program that simultaneously builds a framework of theory and abstraction of data collected based on the findings of meaning on the natural background in the field. By applying a good management system can improve the hard skills and soft skills of vocational graduates in order to get provisions to go to the world of work in accordance with what is needed by the industry or able to entrepreneurship independently. The management system that needs to be implemented includes several aspects, including: (1) Planning, (2) Organizing, (3) Implementation (actuating), (4) Supervision (controlling) and evaluation of programs. Supporting factors and inhibiting the implementation of Teaching Factory Competence of Technical Expertise and Motorcycle Business Vocational High School in Tulungagung Regency of East Java, include: (1) Internal support factors, (2) External support factors, (3) Internal inhibitory factors, and (4) inhibitory factors.